A review on organic–inorganic hybrid nanocomposite membranes: a versatile tool to overcome the barriers of forward osmosis. Issue 18 (12th March 2018) - Sun, Wanying; Shi, Jie; Chen, Cheng; Li, Nan; Xu, Zhiwei; Li, Jing; Lv, Hanming; Qian, Xiaoming; Zhao, Lihuan
Abstract : Nanocomposite forward osmosis (FO) membranes have attracted increasing attentions recently and showed great comprehensive performance. Various modification methods have been employed to incorporate inorganic nanomaterials to FO membranes. Abstract : Forward osmosis (FO) processes have recently attracted increasing attention and show great potential as a low-energy separation technology for water regeneration and seawater desalination. However, a number of challenges, such as internal concentration polarization, membrane fouling, and the trade-off effect, limit the scaleup and industrial practicality of FO. Hence, a versatile method is needed to address these problems and fabricate ideal FO membranes. Among the many methods, incorporating polymeric FO membranes with inorganic nanomaterials is widely used and effective and is reviewed in this paper. The properties of FO membranes can be improved and meet the demands of various applications with the incorporation of nanomaterials. This review presents the actualities and advantages of organic–inorganic hybrid nanocomposite FO membranes. Nanomaterials applied in the FO field, such as carbon nanotubes, graphene oxide, halloysite nanotubes, silica and Ag nanoparticles, are classified and compared in this review. The effects of modification methods on the performance of nanocomposite FO membranes, including blending, in situ interfacial polymerization, surface grafting and layer-by-layer assembly, are also reviewed. The outlook section discusses the prospects of organic–inorganic hybrid nanocomposite FO membranes and advanced nanotechnologies available for FO processes. This discussion may provide new opportunities for developing novel FO membranes with high performance.